2012
DOI: 10.1007/s00586-012-2499-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted pedicle screw placement: lessons learned from the first 102 patients

Abstract: Introduction Surgeons' interest in image and/or robotic guidance for spinal implant placement is increasing. This technology is continually improving and may be particularly useful in patients with challenging anatomy. Only through careful clinical evaluation can its successful applications, limitations, and areas for improvement be defined. This study evaluates the outcomes of robotic-assisted screw placement in a consecutive series of 102 patients. Methods Data were recorded from technical notes and operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(146 citation statements)
references
References 23 publications
1
143
0
2
Order By: Relevance
“…duration of the process in patients who undergo multi-level instrumentation is reduced because of the decrease in the period typically lost during x-ray control and determination of screw location. The superiority of the system is evident in percutaneous interventions, in patients who undergo deformity surgery and in cases of recurrence (10,11,33). In our study, the mean surgical duration was 46.1 minutes in Group A patients as opposed to 73.2 minutes in Group B patients.…”
Section: Resultsmentioning
confidence: 99%
“…duration of the process in patients who undergo multi-level instrumentation is reduced because of the decrease in the period typically lost during x-ray control and determination of screw location. The superiority of the system is evident in percutaneous interventions, in patients who undergo deformity surgery and in cases of recurrence (10,11,33). In our study, the mean surgical duration was 46.1 minutes in Group A patients as opposed to 73.2 minutes in Group B patients.…”
Section: Resultsmentioning
confidence: 99%
“…In this subanalysis, 577 (89.3%) were GRS Grade A; 58 (9.0%) were GRS Grade B; 9 (1.4%) were GRS Grade C; and 2 (0.3%) were GRS Grade D. Hu and colleagues published a series of papers retrospectively assessing pedicle screw accuracy. [9][10][11] In their first paper, 10 accuracy was evaluated using fluoroscopy in 95 patients with 960 screws placed using the Mazor robot (note that accuracy was not graded in all 102 patients; in the other 7 the screw placement was aborted). Of these, 949 (98.9%) were deemed to be accurate.…”
Section: Accuracy Of Spinal Instrumentationmentioning
confidence: 99%
“…5,10,12,15,22,24,27,29 Devito et al found that the ability to place screws robotically was 83.7% in their total cohort, but increased to a 90.8% execution rate when they looked at their most recent procedures. 5 In addition, time per screw placement decreased from 13.5 minutes for single-level cases (4 minutes per screw in multilevel cases) to 10.6 minutes (2 minutes in multilevel cases).…”
Section: Learning Curvementioning
confidence: 99%
“…Although measurement techniques are not standardized, the estimated malposition rates of conventional screw placement in studies such as those conducted by Kosmopoulos and Schizas and Hicks et al are much higher than those of current retrospective robotics studies. 9,12,20 Hu et al 14 conducted another important case series of 102 consecutive patients in whom the SpineAssist was used, which yielded similarly high accuracy rates. In their investigation 949 (98.9%) of 960 robotically placed screws were successfully positioned and 11 were malpositioned, presumably due to incorrect onset of trajectory.…”
Section: 37mentioning
confidence: 99%
“…Retrospective analyses of robot-assisted cohorts have overall demonstrated very high accuracy rates in large numbers of screw placements. 9,14,15 Furthermore, in 2013 Hu and Lieberman 13 contended that the successful placement of pedicle screws with robotic assistance follows a learning curve that increases with surgeons' experience. In a consecutive cohort study of 174 patients who underwent pedicle screw placement by the same surgeon, accuracy rates increased from 82% in the first 30 patients to 93%, 91%, and 95%, respectively, in the following groups of 30 patients.…”
Section: 37mentioning
confidence: 99%